INTEGRASI NILAI-NILAI ISLAM DALAM PENGEMBANGAN ILMU PENGETAHUAN PADA ERA SOCIETY 5.0 - Fakhri Muhammad Ario Putra; Al Anshari; Irmawati Irmawati (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study examines the integration of Islamic values in the development of science and technology in the Society 5.0 era through a qualitative literature study. The research analyzes three main aspects: (1) the concept of tadabbur alam (contemplation of nature) in the Qur'an as an epistemological foundation, (2) critique of secular science from a tawhidic paradigm perspective, and (3) implementation models in Islamic higher education. Findings reveal that the Qur'an provides a comprehensive epistemological framework connecting empirical observation, rational reasoning, and spiritual internalization. Case studies at UIN Bandung and UIN Surabaya demonstrate successful curriculum integration models such as "Revelation Guides Science" and "Integrated Twin Towers." The study concludes that Islamic epistemology offers solutions to contemporary challenges including ecological crises, technological ethics, and meaning crises in modern science. Strategic recommendations are proposed for policy makers, Islamic universities, and technology developers to operationalize this integration. Keywords : Islamic epistemology, Ccience integration, Society 5.0, Tadabbur alam, Tawhidic paradigm